Optimal aircraft scheduling for aircraft departures - Goh, Bibiana Wan Fang (2015)
With many low cost carriers in the market today, it is becoming increasingly easier and cheaper to fly. To quote AirAsia’s slogan, “now everyone can fly”. It is true that with more low cost carriers, everyone can fly. However, the increase in supply of air travel is due to the increasing demand for air travel. It is speculated that with rising business confidence and economic stability, global air travel demand will continue to increase over the years. The continued growth of the aviation industry will hence require significant improvements to the infrastructure of existing systems as well as implementation of new and updated systems. Air traffic flow management takes into account the safety and efficiency of the entire air traffic network while simultaneously striving to strike a balance between demand and capacity. This paper aims to address the problem of minimizing the cost of delay of aircrafts in a small network of departures subjected to separation constraints. The complexity of the problem is also addressed and the model will be intended to solve a small-scale network of aircrafts using Microsoft Excel Solver.